Determining PAUD Teachers’ Capability To Develop Sociable Learning Model Through Traditional Sundanese Games. - Solihin Ichas Hamid; Tuti Istianti; Mohamad Helmi Ismail (International Journal Of Community Service, 2021)
The application of the Sociable Learning Model has strong relevance as a solution to the problem of early childhood social behavior these days. Meanwhile, the role of Early Childhood Education teachers who have crucial value for Early Childhood cannot be well maximized due to the various restrictions as an effort to handle COVID-19 cases in Indonesia. The implementation of training on the development of the Sociable Learning Model through Traditional Sundanese Games in West Java requires a mapping foundation of the teacher's experiences so that it can provide some meaningful and appropriate resources for further treatments. To accommodate the required data collections, the holding of the workshop is needed to accommodate the variety of teacher's perceptions on the Social Citizenship development efforts in the Early Childhood Education setting that can be a starting point to find out the teacher's basic understanding of the development of social civic behavior in PAUD. The exploration effort is has been carried out by spreading questionnaires to workshop participants to collect various teacher perceptions related to innovations in the development of Social Citizenship Behavioral Skills (PrSKn) based on traditional Sundanese games. Keywords: PrSKn, Sundanese traditional games, Teachers' Competency.